The Effect of Work Experience, Supervision by Supervisors, and Integrity on Employee Performance - Hendri Gunawan; Syamsir Syamsir (Publik : (Jurnal Ilmu Administrasi), 2026)
This study aims to analyze the influence of work experience, leadership supervision, and integrity on employee work achievement at the Environmental Agency of Kerinci Regency. The research employed a quantitative approach using path analysis, involving a population of 71 employees, of whom 70 respondents were selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through path analysis consisting of two sub-structures. The findings indicate that: (1) work experience does not have a direct and significant effect on work achievement (β = -0.0145, p = 0.883), but exerts a significant indirect effect through integrity as a mediating variable (indirect effect = 0.2577, Sobel Z = 3.352, p = 0.001); (2) leadership supervision does not directly and significantly affect work achievement (β = 0.1533, p = 0.125), yet demonstrates a significant indirect effect through integrity (indirect effect = 0.2674, Sobel Z = 3.435, p = 0.001); (3) integrity has a positive and significant direct effect on work achievement (β = 0.6419, t = 5.794, p = 0.000), making it the strongest predictor in the model; (4) work experience positively and significantly influences integrity (β = 0.4014, t = 4.170, p = 0.000); and (5) leadership supervision positively and significantly influences integrity (β = 0.4166, t = 4.327, p = 0.000). Furthermore, the model explains 52.63% of the variance in employee work achievement (R² = 0.5263). These findings confirm that integrity serves as a full mediating variable in the relationship between work experience and work achievement, and as a partial mediating variable in the relationship between leadership supervision and work achievement. Therefore, strengthening employee integrity programs is considered a key strategic recommendation to improve employee work achievement within the agency.